Late Cretaceous uplift in the Malargüe fold-and-thrust belt (35°S), Southern Central Andes of Argentina and Chile - Mescua, Jose Francisco (2013)
The Cordillera de los Andes is the typical example of a subduction-related orogen. Its present topography is the result of post-Miocene uplift, however, Andean compressional deformation and uplift started in the Late Cretaceous, as increasingly recognized in different sectors of the mountain belt. We present evidences of a Late Cretaceous event of compressional deformation in the southern Central Andes (35ºS), reflected in syn-orogenic foreland basin deposits assigned to the Neuquén Group in Argentina and the Brownish-Red Clastic Unit in Chile. Comparison of the facies of these units allows us to recognize a sector proximal to the Late Cretaceous orogenic front, a distal sector with sediment provenance from the forebulge and a western sector where the sediments where deposited within the Late Cretaceous mountain belt. On this basis, we assign the orogenic front to an inverted Jurassic normal fault, the Río del Cobre fault, and reconstruct the structure of the easternmost Late Cretaceous Andes at this latitude. The change in the location of the orogenic front north and south of 35ºS allows us to recognize a long-lived change in behavior in Andean evolution in this sector, which correlates with a change in the shape and the deposits of Mesozoic Neuquén basin.